Development of a Hydrogeological conceptual model and groundwater modeling for the Selangor basin, Malaysia - Abu Hassan, Nur Hidayu (2018)
Exploitation demand in surface water for various purposes in Malaysia has been gradually increasing. This issue is very concerning as it involve large scale purposes; especially in agricultural activities and industrial purposes. Hence, it is important to acknowledge the need of a sustainable alternative water supply. Groundwater as water supply is not common in Malaysia. The lack of research and expertise on groundwater aquifer area has led to minimal usage of groundwater. Despite of the limited data information available, this study intends to develop a groundwater flow model within the interest area. However, to achieve this goal, it is important to determine the geological condition of the study area and develop a proper hydrogeological conceptual model to represent the accurate real world conditions and then do a simulation to observe the natural groundwater pattern. The geological condition was determined by the borehole log lithology, and the applicability of the lithology has been confirmed by the geophysical study. A total of six layers which were silty clay; sand and gravel; sandstone; shale and schist with solid granite underlain the subsurface formation as bedrock. The development of hydrogeological conceptual model requires several model input to be included; hydrological data, meteorological data and necessary boundary conditions. Calibration of conceptual model was made with correlation coefficient 0.975 and normalized RMS with 14.18%. Validation of model cannot be made because it requires two set of data with different time period. However, validation should not be seen as end process but as the entire process involved. Groundwater flow mass balance graph has been determined. Input parameters that effects the flow were constant head, river leakage, recharge and ET. Simulation of groundwater flow model gives water table elevation contour and groundwater flow direction. The movement of groundwater direction can be observed flowing from higher hydraulic gradient (high water table elevation) towards lower hydraulic gradient (low water table elevation).